Engineering the surface of graphene oxide with bovine serum albumin for improved biocompatibility in Caenorhabditis elegans. Issue 11 (13th October 2020) - Sivaselvam, S.; Mohankumar, A.; Thiruppathi, G.; Sundararaj, P.; Viswanathan, C.; Ponpandian, N.
Abstract : We have developed a safer GO formulation by decorating its surface with BSA and characterized its biological effect using C. elegans . The GO-BSA mitigates the toxic effect of bare GO. This provides insight into the de novo design of safer nanomaterials. Abstract : Graphene oxide (GO) has been extensively studied for its potential biomedical applications. However, its potential risk associated with the interactions of GO in a biological system hampers its biomedical applications. Therefore, there is an urgent need to enhance the biocompatibility of GO. In the present study, we decorated the surface of GO with bovine serum albumin (GO-BSA) to mitigate the in vivo toxic properties of GO. An in vivo model Caenorhabditis elegans has been used to study the potential protective effect of BSA decoration in mitigating GO induced toxicity. The BSA decoration on the surface of GO prevents the acute and prolonged toxicity induced by GO in primary and secondary organs by maintaining normal intestinal permeability, defecation behavior, development, and reproduction. Notably, GO-BSA treatment at 0.5–100 mg L −1 does not affect the intracellular redox status and lifespan of C. elegans . Reporter gene expression analysis revealed that exposure to GO-BSA (100 mg L −1 ) did not significantly influence the nuclear accumulation and expression patterns of DAF-16/FOXO and SKN-1/Nrf2 transcription factors and their downstream target genes sod-3, hsp-16.2, ctl-1, 2, 3, gcs-1, and gst-4 when compared to exposure to pristine GO. Also, quantitative real-time PCR results showed that GO-BSA did not alter the expression of genes involved in regulating DNA damage checkpoints ( cep-1, hus-1 and egl-1 ) and core signaling pathways of apoptosis ( ced-4, ced-3 and ced-9 ), in contrast to GO treatment. All these findings will have an impact on the future development of safer nanomaterial formulations of graphene and graphene-based materials for environmental and biomedical applications.